Performance related emotion from a task perspective : an application of individual zone of optimal functioning model (IZOF) in Kelantan Football team - Hamzah, Nurul Azuar (2006)
Emotion is one of the important components of total human functioning which can influence the athlete's performance. The Individual Zone of Optimal Functioning (IZOF) model (Hanin, 2000) holds that athlete's performance related emotion are unique and therefore interventions should be individually designed. The aim of the present study was to examine the idiosyncratic nature of emotion content and intensity among athletes and to find out if the emotion intensity for the athlete is significantly different among individuals playing in similar and different positions. Participants consisted of 23 football athletes aged 21-30 years, who represent Kelantan state at the competitive level. Findings lent support that each athlete . within a team has individual emotion content and intensity, which are unique and different from one another. The trend of the result showed significant differences (p<O. 05) between athletes playing in similar position and executing similar task, implying idiosyncratic nature of emotion intensity. No significant differences (p>0.05) were observed in emotion intensity, among athletes, playing in different positions. However, an exception in the case of positive-optimal (P+) emotion was noted. The patterns of emotion intensities reflected that the emotion profiles had specific shape, typical for best (iceberg shape) and worst (cavity shape) performance. Roughly designed optimal zones were made for each athlete so as to help the coach and psychologist in emotion regulation, as part of psychological assistance.